Meningkatkan Antusiasme dan Hasil Belajar Siswa dengan Model Picture and Picture Berbantuan Media Puzzle pada Muatan Matematika, Bahasa Indonesia, dan PPKn Kelas 1 SD - Bekti Ariyani; Wasitohadi Wasitohadi; Theresia Sri Rahayu (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The research conducted aims to determine of the picture and picture model applied to students who are hyperactive to increase enthusiasm and increase learning outcomes. The instruments used in this study are teacher activity sheets, student test results and learning activity documents. Thematic learning outcomes of students in the pre-cycle were only 3 (three) students (11%) who were completed from 27 (twenty seven) students, in first cycle only 10 (ten) students (37%) were completed from 27 (twenty seven) students, while in second cycle reached 100% who got complete score of 27 (twenty seven) students. This means that the learning process with the Picture and Picture model runs well. By studying the results of the study, the authors can conclude that the implementation of the learning steps using the Picture and Picture model can increase the learning outcomes in Salatiga 10 Elementary School.